Caracterización de mieles del bosque de Caldén pampeano - Tamame, Angélica; Brun, Josefina; Morete, Macarena; Paredes, Silvia Susana; Felice, Guillermo; Tobal, Nicolas; Urretavizcaya, Mariana; Audisio, Santiago; Paesani, Belén; Fernández, Jésica; Schall, Franco (Editorial de la Universidad Nacional de La Pampa, 2025)
Poster y resumen